Risk Regulation in High-Conflict Parenting. Issue 6 (18th August 2018) - Amundson, Jon K.; Short, Jennifer
ABSTRACT: That "there is no gathering of roses without risking the thorns" might be the simplest way to think of the paradox of relationship. Risk regulation as psychological mechanism minimizes rejection (thorns) and maximizes assurance (roses). In the article, the social psychology of risk regulation is set in the context of divorce and high-conflict parenting. Risk regulation provides not only guidance for treatment, but also a conceptual framework for professional opinion in forensic evaluation and legal consideration.